(untitled) (Annals of Medical Research, 2025)
Aim: This study aims to evaluate the effect of variables such as gastroesophageal reflux disease (GERD), bruxism, plaque index, and age on erosive wear occurring on the palatal surfaces of maxillary anterior teeth, and to objectively measure this wear using the Anterior Clinical Erosive Classification (ACEC). Materials and Methods: A total of 507 individuals were included. Participants completed self-report questionnaires regarding the presence, previous diagnosis, disease duration, and medication use. Bruxism was assessed through self-report and clinical examination. Erosive wear on maxillary anterior teeth palatal surfaces was measured using ACEC, and plaque accumulation using the Silness and Löe Plaque Index. Statistical analyses included independent sample t-tests and Spearman/Pearson correlation coefficients. Significance was set at p<0.05. Results: Reflux disease was detected in 20.9% of the participants in the study. ACEC scores of individuals reporting reflux symptoms were found to be significantly higher compared to healthy individuals (p<0.05). ACEC scores were also found to be significantly higher in individuals with bruxism than those of without bruxism. In contrast, the plaque index did not show a significant difference between the groups. Additionally, a significant and positive relationship was found between the duration of reflux and ACEC scores (r=0.281, p<0.01). ACEC scores were observed to be higher in individuals receiving reflux treatment compared to those not using medication. Conclusion: These findings indicate that reflux affects not only the gastrointestinal system but also oral and dental health and emphasize the importance of early diagnosis and intervention for dental erosion in individuals with reflux symptoms. Our study reveals the usability of the ACEC in large populations and sheds light on the multifactorial etiology of dental erosion. It also highlights the need to consider the potential abrasive effects of medications used in reflux treatment.